How firms navigate cooperation and competition in nascent ecosystems - Hannah, Douglas P.; Eisenhardt, Kathleen M. (Strategic Management Journal, 2018)
Research Summary Despite a wealth of research on competitive and cooperative strategy, gaps remain with respect to how firms successfully navigate cooperation and competition over time. This is especially true in ecosystems, in which firms depend on one another to collectively provide components and create value for consumers. Through an in‐depth multiple case study of five firms in the U.S. residential solar industry from 2007 to 2014, we induct a theoretical framework that explains how firms navigate nascent ecosystems over time. We identify three strategies, each with a distinct balance of cooperation and competition, as well as unique advantages, disadvantages, and required capabilities. Overall, we contribute to research on ecosystem strategy, crystallize the pivotal role of bottlenecks, and shed light on the dynamic interplay of cooperation and competition. Managerial Summary Competition and cooperation are fundamental to strategy, and often closely intertwined. But how firms navigate and balance cooperation and competition over time, especially in ecosystems where firms depend on one another to deliver value to consumers, is unclear. In this article, we conduct an in‐depth multiple‐case study of five firms in the U.S. residential solar industry to examine how firms can successfully navigate nascent ecosystems over time. We identify three distinct strategies, each with a distinct balance of cooperation and competition, and examine the unique advantages, disadvantages, and required capabilities of each. In doing so, we also contribute novel insights into the evolution of ecosystems and bottlenecks.